Systemic immunomodulatory treatments for atopic dermatitis: protocol for a systematic review with network meta-analysis. Issue 8 (29th August 2018) - Drucker, Aaron Mark; Ellis, Alexandra; Jabbar-Lopez, Zarif; Yiu, Zenas Z N; Arents, Bernd W M; Burton, Tim; Spuls, Phyllis I; Küster, Denise; Schmitt, Jochen; Flohr, Carsten
Abstract : Introduction: There are numerous new systemic treatments for atopic dermatitis in various stages of development and most are being compared with placebo rather than active comparators. In order to understand the relative efficacy and safety of existing and new treatments for atopic dermatitis, robust mixed comparisons (ie, direct and indirect) would be beneficial. To address this gap, this protocol describes methods for a systematic review and network meta-analysis of systemic treatments for atopic dermatitis. Methods and analysis: We will update the search of a previous systematic review, including searches of the Cochrane Central Register of Controlled Trials, MEDLINE, Embase, Latin American and Caribbean Health Science Information database and the Global Resource of EczemA Trials database in addition to clinical trial protocol registries. Title, abstract and full paper screening as well as data extraction will be conducted in duplicate by independent researchers. Primary outcomes include efficacy with regards to clinician-reported signs and patient-reported symptoms and safety with regards to withdrawal from treatment due to adverse events and the occurrence of serious adverse events. Secondary outcomes will include change in quality of life and itch severity. Where possible and appropriate, network meta-analysis will be performed for each outcome using a random-effects model within a Bayesian framework. If appropriate, the review will be transitioned to a living review with continuous updating of the analysis. Ethics and dissemination: Dissemination in a peer-reviewed scientific journal is planned. PROSPERO registration number: CRD42018088112; Pre-results.